Characterisation of synthesised trimetallic nanoparticles and its influence on anaerobic digestion of palm oil mill effluent - Jadhav, Pramod; Krishnan, Santhana; Kamyab, Hesam; Zaied, Khalid; Bhuyar, Prakash; A. W., Zularisam; Mohd Nasrullah, Zulkifli (Elsevier, 2023)
The augmentation of biogas production can be achieved by incorporating metallic nanoparticles as additives within anaerobic digestion. The objective of this current study is to examine the synthesis of Fe–Ni–Zn and Fe–Co–Zn trimetallic nanoparticles using the co-precipitation technique and assess its impact on anaerobic digestion using palm oil mill effluent (POME) as carbon source. The structural morphology and size of the synthesised trimetallic nanoparticles were analysed using a range of characterization techniques, such as X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), Scanning electron microscopy (SEM), and Energy-dispersive X-ray spectroscopy (EDX). The average size of Fe–Ni–Zn and Fe–Co–Zn were 19–25.5 nm and 19.1–30.5 nm respectively. Further, investigation focused on examining the diverse concentrations of trimetallic nanoparticles, ranging from 0 to 50 mgL−1. The biogas production increased by 55.55% and 60.11% with Fe–Ni–Zn and Fe–Co–Zn trimetallic nanoparticles at 40 mgL−1 and 20 mgL−1, respectively. Moreover, the lowest biogas of 11.11% and 38.11% were found with 10 mgL-1 of Fe–Ni–Zn and Fe–Co–Zn trimetallic nanoparticles. The findings of this study indicated that the trimetallic nanoparticles exhibited interactions with anaerobes, thereby enhancing the degradation process of palm oil mill effluent (POME) and biogas production. The study underscores the potential efficacy of trimetallic nanoparticles as a viable supplement for the promotion of sustainable biogas generation.